TREDtwo community service program: Center orientation module - Amistoso, Marjorie G. (Animo Repository, 2014)
This module is prepared for the TREDTWO Community Service Program of DLSU-Manila. It is a three hour session conducted by the representatives of COSCA's institutional/community partners. It is intended as a sharing activity among the students, facilitators and community leaders. It is conducted before the actual community service of students in their chosen deployment area and may either be on-site or in the campus.